Motor training at 3 months affects object exploration 12 months later. Issue 6 (21st December 2015) - Libertus, Klaus; Joh, Amy S.; Needham, Amy Work
Abstract: The development of new motor skills alters how infants interact with objects and people. Consequently, it has been suggested that motor skills may initiate a cascade of events influencing subsequent development. However, only correlational evidence for this assumption has been obtained thus far. The current study addressed this question experimentally by systematically varying reaching experiences in 40 three‐month‐old infants who were not reaching on their own yet and examining their object engagement in a longitudinal follow‐up assessment 12 months later. Results revealed increased object exploration and attention focusing skills in 15‐month‐old infants who experienced active reaching at 3 months of age compared to untrained infants or infants who only passively experienced reaching. Further, grasping activity after – but not before – reaching training predicted infants' object exploration 12 months later. These findings provide evidence for the long‐term effects of reaching experiences and illustrate the cascading effects initiated by early motor skills. Abstract : Reaching experiences were systematically manipulated in 3‐month‐old infants using ?Sticky Mittens'. When assessed 12 months after their training, infants showed increased grasping and object directed attention skills. Early reaching experiences seem to initiate developmental cascades that facilitate subsequent learning and exploration.